Legendaries of Islamic political thought - Shuriye, Abdi Omar (Dar At-Tajdid Litiba'a Wa Al-Nashr Wa Al-Tarjama, 2005)
The complexity of current global political set up and its effect on the Muslim world summons revisit on various aspects of Muslim political ideas. International political conflicts of the day are associated with socio-political interests, identity, religion, and culture. Impacts of globalization, religious tolerance, delusion on Western-Muslim relations are also few interplaying factors in contemporary Muslim political thought. One would persuasively argue that existing Muslim political tribulations have no bases in the teachings of Islam as a doctrine of faith. The key drawbacks however rest in the nerves that configure the cognitive and imaginative culture of Muslim weltanschauung order. The purpose of this work, which is the first of a series on diverse themes of political thought, is to reexamine the mainstream scholarship and its contributions to Muslim political mechanism. I wish to acknowledge the library of International Islamic University Malaysia, my colleagues in the Kulliyah, and my wife.